2004
DOI: 10.1088/0953-8984/16/43/l01
|View full text |Cite
|
Sign up to set email alerts
|

A study of the deep structure of the energy landscape of glassy polystyrene: the exponential distribution of the energy barriers revealed by high-field electron spin resonance spectroscopy

Abstract: The reorientation of one small paramagnetic molecule ( spin probe ) in glassy polystyrene ( PS ) is studied by high-field Electron Spin Resonance spectroscopy at two different Larmor frequencies ( 190 and 285 GHz ). The exponential distribution of the energy-barriers for the rotational motion of the spin probe is unambigously evidenced at both 240 K and 270 K. The same shape for the distribution of the energybarriers of PS was evidenced by the master curves provided by previous mechanical and light scattering … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
38
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 49 publications
5
38
0
Order By: Relevance
“…Buchenau confirmed that conclusion by comparing results from several techniques covering a wide time window from 1Hz up to about 100GHz [18]. The same result has been reached by HF-EPR [10,11,19].…”
Section: Introductionsupporting
confidence: 67%
See 4 more Smart Citations
“…Buchenau confirmed that conclusion by comparing results from several techniques covering a wide time window from 1Hz up to about 100GHz [18]. The same result has been reached by HF-EPR [10,11,19].…”
Section: Introductionsupporting
confidence: 67%
“…The shape of the energy-barriers distribution g(E) in glasses has been extensively investigated via experiments [8,10,11,16,17,[19][20][21][22][23][24], theories [25][26][27][28][29] and simulations [30]. Basically, two different distributions are usually recovered, the gaussian distribution [8,16,20,21,24,25,30,31] and the exponential distribution [8,10,11,17,19,22,[26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations